2006
DOI: 10.1530/eje.1.02130
|View full text |Cite
|
Sign up to set email alerts
|

Are serum leptin and the Gln223Arg polymorphism of the leptin receptor determinants of bone homeostasis in elderly men?

Abstract: Objective: Across studies it has been suggested that leptin intervenes as a regulator of bone metabolism. This study assesses the contribution in elderly men of leptin and the Gln223Arg leptin receptor gene (LEPR) polymorphism to the variation in bone homeostasis, in relation to body composition and free estradiol as major confounders. Design: We performed cross-sectional (n ¼ 270) and longitudinal (mean follow-up 3.4 years, n ¼ 214) evaluations in elderly men. Methods: Serum leptin, LEPR genotype, baseline bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
0
14
1
2
Order By: Relevance
“…Lorentzon et al [48] have concluded that leptin is a negative independent predictor of BMD, and Crabbe et al [49] have found that serum leptin is positively associated with bone loss. It seems, therefore, that further work is needed to clarify the role that the decrease in serum leptin after weight loss may play in the metabolic bone changes that develop simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Lorentzon et al [48] have concluded that leptin is a negative independent predictor of BMD, and Crabbe et al [49] have found that serum leptin is positively associated with bone loss. It seems, therefore, that further work is needed to clarify the role that the decrease in serum leptin after weight loss may play in the metabolic bone changes that develop simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In a study population of 219 adult Korean males, carriers of the Gln223 allele had higher bone mineral density at the lumbar spine compared with subjects not carrying the allele (30). In 270 European men over 70 yr, however, no association was found between Gln223Arg and BMD changes at the hip and forearm (31). Therefore, the contribution of LEPR alleles to bone mass acquisition remains unknown.…”
Section: Eptin Has Recently Been Identified As An Importantmentioning
confidence: 99%
“…У молодых китаянок, моло-дых корейских и европейских мужчин Gln223Arg-поли-морфизм был ассоциирован с пиком костной массы [28,35]. Среди 270 взрослых европейцев были выявлены ас-социация Gln223Arg-полиморфизма с костной щелоч-ной фосфатазой и отсутствие связи с МПКТ [36]. Интер-претация связи полиморфизмов гена LEPR с МПКТ за-труднена из-за плейотропных функций системы лепти-на.…”
Section: распределение аллелей и генотипов Lep (A19g) Lepr (Gln223arunclassified